HUBUNGAN ANTARA KAMPANYE DENGAN SIKAP REMAJA - Michael Hartono; Rizky Fauzi (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2019)
Tik Tok’s launched a campaign that called #AnakGenius. The paradigm of this research was positivistic. The approach of this research was Quantitative. The method of this research was eksplanatif. Based on the background, the purpose of this research was to find the relationship between the campaign anak genius among South Tangerang Junior High School 17 Students Bekasi. The concept that used of this research were campaign and behavior. The subjects of this research were 92 respondent. The results showed that there was a validity of KMO’s score of Campaign (0.812) and behavior (0.751). There was a reliable of Cronbach’s Alpha score of campaign 0.824 and behavior 0.769. P score of this research was 0.619. This indicates that there are strong relationships between the campaign AnakGenius among South Tangerang Junior High School 17 Students.